Using artificial intelligence for the control of medium voltage substations - Melvin Avala, S.; Botura Jr., Galdenoro; Maldonado A, Oscar Armando [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2002)
This paper introduces a method for the supervision and control of devices in electric substations using fuzzy logic and artificial neural networks. An automatic knowledge acquisition process is included which allows the on-line processing of operator actions and the extraction of control rules to replace gradually the human operator. Some experimental results obtained by the application of the implemented software in a simulated environment with random signal generators are presented.
Keywords: Artificial Intelligence; Artificial Neural Networks; Fuzzy Logic; Artificial intelligence; Electric generators; Fuzzy sets; Neural networks; Topology; Voltage control; Energy deficit; Electric substations